2018
DOI: 10.1016/j.jtho.2018.08.513
|View full text |Cite
|
Sign up to set email alerts
|

MA23.03 Risk Assessment for Indeterminate Pulmonary Nodules Using a Novel, Plasma-Protein Based Biomarker Assay

Abstract: Background: To reduce overdiagnosis and overtreatment of noncancerous pulmonary nodules found on CT scans, a noninvasive and easily administered test is needed to assess clinically significant disease risk. Such an assay should also accurately inform whether additional aggressive evaluation, including lung biopsy or thoracic surgery, is warranted. Objective: To determine the performance of a novel, plasma-based multiplexed protein test model when compared to the Veterans Affairs Clinical Factors Model (VA mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Regular screening allows the detection of early and localized lung cancer 5 . Several studies have shown that pulmonary nodules are early and potentially curable form of lung cancer, which can be classified as either solid or sub‐solid 6‐8 . As the most common type of nodules, solitary pulmonary nodules (SPNs) are divided into solid and sub‐solid, with a diameter of less than 3 cm and surrounded by pulmonary parenchyma without any other abnormalities 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Regular screening allows the detection of early and localized lung cancer 5 . Several studies have shown that pulmonary nodules are early and potentially curable form of lung cancer, which can be classified as either solid or sub‐solid 6‐8 . As the most common type of nodules, solitary pulmonary nodules (SPNs) are divided into solid and sub‐solid, with a diameter of less than 3 cm and surrounded by pulmonary parenchyma without any other abnormalities 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the multi-reaction-monitoring proteomic signature (MRM) that VUMC contributed specimens, clinical experience, scientific expertise and biostatistics is also now available commercially from Biodesix as the NodifyXL2 test [25]. The magnetic nanosensor based biomarker detection platform for which VUMC provided a validation sample set and expertise is now commercially available from MagArray (Malpitas, CA) [18,19,50].…”
Section: Industry Partnerships Using Biospecimensmentioning
confidence: 99%
“…Label-free techniques such as surface plasmon resonance (SPR), quartz crystal microbalance, wave-guided interferometry, and mass spectrometry (MS) have been used for biomarker quantification. While MS has been exceedingly valuable in the biomarker discovery phase, relative instrument complexity and difficulty with quantification make its use in clinical validation unattractive. Multiplexed MRM/MS targeted assays using stable isotope-labeled peptide standards for quantitation show promise as clinical diagnostic assays, yet low-throughput remains a challenge. …”
Section: Introductionmentioning
confidence: 99%